Impact of perceived organizational support on work engagement: Mediating mechanism of thriving and flourishing - Muhammad Yasir Imran; Natasha Elahi; Ghulam Abid; Fouzia Ashfaq; Sehrish Ilyas (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
Based on organizational support theory, this study examined the indirect influence of perception of organizational support on employee work engagement with the mediating influence of flourishing and thriving at work. Data were collected by utilizing the self-administered questionnaires related to study variables in two different time periods. Using PROCESS Macros on an actual sample of 638 employees, the study found that perceived organizational support was positively associated with employee flourishing, thriving, and work engagement. Moreover, perceived organizational support indirectly influences work engagement via thriving and flourishing. The study provides many insights into evolving constructs (i.e., thriving and flourishing) and examines how organizations can create the psychological state and well-being (hedonic and eudemonic) of employees through the perception of organizational support.
Keywords: 650; perceived organizational support; thriving at work; flourishing; work engagement